2023
DOI: 10.2147/ijn.s394366
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Nozzle 3D Printed Nano-Hydroxyapatite Scaffold Loaded with Vancomycin Sustained-Release Microspheres for Enhancing Bone Regeneration

Abstract: Background Successful treatment of infectious bone defect remains a major challenge in the orthopaedic field. At present, the conventional treatment for infectious bone defects is surgical debridement and long-term systemic antibiotic use. It is necessary to develop a new strategy to achieve effective bone regeneration and local anti-infection for infectious bone defects. Methods Firstly, vancomycin / poly (lactic acid-glycolic acid) sustained release microspheres (VAN/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Their implantation into cranial defects in ovariectomized mice to show in vivo new bone formation in an osteoporotic model is subject of a future work. Reports on the implantation of 3D printed PLA-HA composite scaffolds in rabbits indicated their effectiveness on repairing bone defects [ 73 , 74 ]. Moreover, the implantation of composite scaffolds comprising PLLA with mineralized strontium-doped hydroxyapatite in rabbits has been reported to promote bone regeneration [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their implantation into cranial defects in ovariectomized mice to show in vivo new bone formation in an osteoporotic model is subject of a future work. Reports on the implantation of 3D printed PLA-HA composite scaffolds in rabbits indicated their effectiveness on repairing bone defects [ 73 , 74 ]. Moreover, the implantation of composite scaffolds comprising PLLA with mineralized strontium-doped hydroxyapatite in rabbits has been reported to promote bone regeneration [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their unique properties, nanoparticles can improve the mechanical properties of hydrogels, enhance surface interactions, and increase drug release rate and bioavailability. The addition of nanoparticles to hydrogels allows better access to tissues through capillaries and more effective delivery of therapeutic drugs to the site of injury ( Li et al, 2023 ).…”
Section: Application Of Biomaterials Scaffolds In Scimentioning
confidence: 99%
“…This fact can be justified by the hydrophilic nature of these scaffolds (contact angle measurements provided in Supplementary Material Figure S1), which can influence the bacterial adherence to the surface of the biomaterial [19]. Maikranz et al showed that S. aureus adheres more strongly to hydrophobic than hydrophilic surfaces [44]. It may then be relevant to consider the hydrophilicity of the biomaterials used to manufacture the scaffolds, as they may play a key role in the initial adhesion of bacteria that help to prevent infections related to their implantation.…”
Section: Antibacterial and Antibiofilm Activitymentioning
confidence: 99%
“…Moreover, despite the fact that the absence of cytotoxicity was confirmed, together with the antibacterial activity of the scaffolds loaded by the three methodologies, the physicochemical properties of the unloaded 3D-printed PLA-HA scaffolds were proven to present a certain degree of antibacterial activity (with an unexpectedly high number of dead bacteria) against S. aureus. In relation to this, several authors have investigated the influence of the surface of a biomaterial on the bacterial adherence [19], which in the case of S. aureus seems to be significantly higher on hydrophobic surfaces [44]. The hydrophilicity of the 3D-printed PLA-HA scaffolds proposed may play a key role in the initial adhesion of bacteria and should be considered as an added advantage for their local prevention of infections.…”
Section: Antibacterial and Antibiofilm Activitymentioning
confidence: 99%